RANCANG BANGUN ALAT PENAKAR DAN PENGEMAS GULA PASIR BERBASIS ARDUINO UNO - Agustina Damayanti; Dedy Hendryadi; Nurwahid Syam (CV. LAJAGOE PUSTAKA, 2023)
This study aims to: (1) Design a valid Arduino Uno-based sugar measuring and packaging tool. (2) Knowing the user's response to the Arduino Uno-based sugar measuring and packaging device. The research method used is Research and Development (Research and Development) is a research method to develop and test products that will later be developed in sugar packaging designs that can assist users in measuring and packing granulated sugar. R&D research methods: Identification of potential problems, information gathering, product design, tool validation, product revision, small group trial, product revision 1, large group trial, product revision 2. Based on the results of this study, it can be concluded that: (1) The design product of the measuring device and packaging for granulated sugar that has been designed based on the assessment of experts and practitioners has been declared valid, with the following profiles, the design of the measuring device and packaging for granulated sugar starts from seeking information through the literature , then do the collection of materials and tools. After the tools and materials have been collected, a product design is carried out to determine a series of component positions, the product that has been designed is made and then validated. The validation results are used as a benchmark for implementation and revision. (2) The user's perception of the arduino uno-based sugar measuring and packaging tool which gets an average value of 81.1% or very positive where this tool is capable of measuring and packing granulated sugar and can be used at the Ical Jaya shop